Exploiting the potential of molecular profiling in Parkinson's disease: current practice and future probabilities. (November 2010) - Mellick, George D; Silburn, Peter A; Sutherland, Greg T; Siebert, Gerhard A
Parkinson's disease (PD) is a common, heterogeneous syndrome diagnosed clinically by the presence of classical neurological symptoms and the absence of 'red flags' that suggest alternative secondary parkinsonian disorders. Neuropathologically, nigrostriatal loss and the presence of proteinaceous inclusions (Lewy bodies) confirm the diagnosis. For PD, molecular profiling promises much but is yet to deliver in terms of breakthroughs for identifying at-risk individuals, detecting disease at early stages, improving diagnostic certainty, prognosticating future outcomes or providing surrogate markers of therapeutic efficacy. Recent, large-scale omics studies, driven by technological advances, have generated terabytes of data but not yet met the goal of developing biomarkers suitable for clinical use in PD. In this article we critically evaluate the recent literature to identify the key roadblocks and realistic opportunities facing researchers interested in utilizing molecular profiling in the clinic to improve the diagnosis and treatment of PD.